Effects of Low- and High-Level Gossypol and Sodium Butyrate Supplementation Under High-Level Gossypol Condition on Growth Performance and Intestinal Health of Hybrid Grouper (Epinephelus fuscoguttatus♀×Epinephelus lanceolatus♂) - Yin, Bin; Liu, Hongyu; Tan, Beiping; Dong, Xiaohui; Chi, Shuyan; Yang, Qihui; Zhang, Shuang (Frontiers in Marine Science, 2021)
The supplementation of gossypol in excess is noted to cause detrimental effects such as the reduction of antioxidant enzymes and disruption of lipid metabolism in animals. Studies regarding the effects of different levels of gossypol are very rare; thus, this study was conducted to evaluate the effects of low and high dietary levels of gossypol and of supplementation with 0.13 % sodium butyrate (NaB) under high gossypol conditions on the growth performance and intestinal health of hybrid grouper (Epinephelus fuscoguttatus♀×Epinephelus lanceolatus♂). Four treatments were used: Feed containing 40% fish meal was used as the control group [fishmeal (FM)], the FM diet plus 0.03% gossypol acetic acid (abbreviated as gossypol) as the low-level gossypol group (gL), FM + 0.15% gossypol was used as the high-level gossypol group (gH), and FM+0.15 % gossypol with 0.13 % NaB as the repair group (gHNaB). All diets were isonitrogenous and isolipidic. The results showed that the gL treatment significantly increased specific growth rate (SGR) and feed utilization; upregulated mRNA levels of distal intestinal transforming growth factor-β1 (tgfβ1), jam, occludin, claudin3, and zo1; and downregulated mRNA levels of il8, ifnγ, and akt. The gH treatment significantly reduced SGR and feed utilization; increased distal intestinal total nitric oxide synthase (NOS) activity and nitric oxide (NO) content; upregulated mRNA levels of distal intestinal tnfα, il1β, il6, ifnγ, caspase2, caspase9, and akt; and downregulated mRNA levels of tgfβ1, jam, and zo1. NaB supplementation significantly increased distal intestinal total NOS activity and NO content; downregulated distal intestinal tnfα, il1β, ifnγ, pi3k p85, and akt mRNA levels; and increased distal intestinal tgfβ1, jam, occludin, and zo1 mRNA levels. Above all, low- and high-level gossypol exhibited positive and negative effects on growth performance, distal intestinal anti-inflammatory capacity, and tight junctions, respectively, in hybrid groupers. NaB supplementation improved distal intestinal anti-inflammatory capacity and tight junctions in hybrid groupers to a certain extent.